Astrophysically relevant experiments on radiation transfer through plasmas with large velocity gradients - Wark, J; Rose, S; Patel, P; Djaoui, A; Renner, O; Hauer, A (1997)
The transfer of radiation through plasmas with large velocity gradients is of relevance to several astrophysical situations, such as supernova explosions, maser operation, and stellar winds. Similar conditions often prevail in laser-produced plasmas, with velocity gradients of order 10(9) s(-1) significantly altering the effective optical depth and line shape. Some of the simplest cases to study experimentally are the hydrogenic resonance lines. Experiments performed in both planar and cylindrical geometry, comparing the observed line profiles with those modeled using a one-dimensional Lagrangian hydrocode, incorporating average-atom nonlocal thermodynamic equilibrium (non-LTE) atomic physics are described. The opacity effects on the ion populations an treated within the escape factor approximation, taking into account the effects of the velocity gradient. The hydrocode gives time- and space-dependent values of the electron and ion densities, excited state fractions, electron and ion temperatures, and velocities, The hydrodynamic output is post-processed with a radiative transfer routine to construct the simulated line shape. Details of the experiments and results are presented, and relevance to the astrophysical situations discussed. (C) 1997 American Institute of Physics.